Leaf Quality :Hyperspectral Imaging Technology - Mary A, Pramila; G, Thippeswamy (International Journal of Engineering and Technology, 2018)
India is a rural nation 70% of the populace relies upon horticulture. Farmers are the backbone of our nation.70% of the economic growth depends on agriculture. The major food crops of India are wheat, corn, rice, barley, sorghum. In this project the concentration is on paddy as it is a main food crop of our state. This project helps us to find whether the leaf is diseased or not and also helps us to find the type of disease in paddy leaf. The agribusiness research of programmed leaf sickness recognition is fundamental research point as it might demonstrate benefits in checking substantial fields of products, and subsequently naturally recognize manifestations of illness when they show up on plant takes off. Digital image processing Advanced is a procedure utilized for improvement of the picture. To enhance farming items programmed recognition of side effects is useful. Â Â